Chitosan and Sodium Alginate: The Potential of Natural Biopolymers of Marine Origin in Development of Biodegradable Packaging Material: Natural Biopolymers in Biodegradable Packaging Material - Reshma, C. S.; Remya, S.; Bindu, J. (Fishery Technology, 2025)
Chitosan and sodium alginate are important natural polymers that are abundant in marine sources. Chitosan is generated from chitin by chemical N-deacetylation and is made up of poly-β-(1→4)-2-amino-deoxy-D-glucopyranose. It is found in the shells of crustaceans, insects, fungi, and also in the scales of fishes. Sodium alginate is a derivative of alginic acid found mostly in marine brown algae, made up of 1,4-β-d-mannuronic (M) and α-l-guluronic (G) acids. Chitosan and sodium alginate are natural, non-toxic, biocompatible and biodegradable polysaccharides. Thus, they have a wide range of uses in food packaging, biomedical applications, and are used to make biodegradable films in various compositions. This review covers chitosan and sodium alginate-based films with various combinations of polysaccharides, protein, essential oil, plant extract and synthetic materials. The incorporation of these materials has improved the physical, mechanical, barrier, antioxidant and antimicrobial properties of the films.